Public Health Status of Arar Village, Sorong Regency, South West Papua - Naibey, Rosdiana; Iyai, Deny A; Yulidia, Herlina; Pesurnay, Yanti; Purnomowati, Happy D (Technium BioChemMed, 2023)
Health Indonesia Program is one of the programs of the 5th Agenda of Nawa Cita, which is to improve the quality of life of Indonesian people. The community of Arar village lives on a small island directly adjacent to Aimas District, Sorong regency. Access to hospital is still limited as a priority for survival. Observations were carried out in Arar Village in February-March 2021. The important things in the observation were the general health conditions. This study was observed the location, population distribution, and survey data on the community. The observations were followed by the 17 indicators of the Sustainable Development Goals. One of the important indicators is health promotion, prosperous life, supporting well-being for all ages. The observation showed that in general the health status of the people of arar village was quite good. On the other side, the biggest obstacle experienced by the local community was health services by health workers still very limited. It is because the distance from Arar Village to Hospital or Health Center quite far. Also, the people complaint health services did not run regularly by the doctors and nurses. Therefore, the people were always to push themselves independently to find the nearest health center or hospital. Lack of health workers affected to people’s hope to make appointment with them for monitor their health status regularly. It has an affect on demotivates people in an era mutual prosperity.